Explore BrainMass
Share

Explore BrainMass

    Sequences and Series of Functions

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    1. Write the following in expanded for then find the sum
    a) ^7(Sigma sign) k=0 (k=1)(k+2)
    b) ^7(Sigma sign) k=4 3k
    Note: The sigma sign does not show up when pasted here. The 7 is on top of the sigma sign and the k= 0 or k=2, respectively, lies below the sigma sign.

    2. Express the following series using sigma notation:
    a) (1 X 0)/2 + (2 X 1)/3 + (3 X 2)/4 + ........ (10 X 9)/11
    b) (1 X 2)/2 + (2 X 3)/4 + (3 X 4)/6 + .......... (8 X 9)/16

    3. Use the Binomial Theorem to expand the following equation:
    a) (2p - 3q)^4
    b) (2p + 1)^4

    4. Find the fifth term in the expansion of (4x + 2y)^7

    5. Find the sum of the following series, or state that the sum does not exist
    a) 12 + 8 + 16/3 + .......
    b) 1/12 + 1/2 + 3 + .........

    6. Find the limit of the following or state that the limit does not exist
    a) (2n - 1)/n^3
    b) ......as n approches infinity of (2n^2)/(n^2 - 1)

    © BrainMass Inc. brainmass.com May 20, 2020, 10:51 pm ad1c9bdddf
    https://brainmass.com/math/basic-algebra/sequences-series-functions-537397

    Solution Preview

    1. ∑_(k=0)^7▒(k+1)(k+2)
    First, since this is summation from k=0 to k=7,
    We could transform the expression into the following:
    ∑_(k=0)^7▒(k+1)(k+2) =(0+1)*(0+2)+(1+1)*(1+2)+(2+1)*(2+2)+(3+1)*(3+2)+(4+1)*(4+2)+(5+1)*(5+2)+(6+1)*(6+2)+(7+1)*(7+2)=1*2+2*3+3*4+4*5+5*6+6*7+7*8+8*9=240

    2. ∑_(k=4)^7▒〖3k=3*4+3*5+3*6+3*7=66〗

    3. a)(1*0)/2+(2*1)/3+(3*2)/4+⋯+(10*9)/11
    First, in the first value, for the two numbers in the numerators, they are 1 and 2 less than denominator respectively.
    Therefore, if k starts from 0, the first number a0=(0+1)*0/(0+2) or (k+1)k/(k+2) in general. ...

    Solution Summary

    Sequences and series of functions are examined.

    $2.19

    ADVERTISEMENT